PERUBAHAN IKLIM DAN KONSEKUENSINYA : POTRET KERENTANAN PANGAN MASYARAKAT PESISIR GILI GEDE INDAH AKIBAT PERUBAHAN IKLIM - wijayanti, ika; Hilmi, Farida; Hakim, Latifa D R; Salsabilla, Sally (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2025)
Pulau Gili Gede is a cluster of islands in the southeast of Lombok Island affected by climate change. The characteristics of coastal communities related to the ocean are influenced by weather factors, along with dependence on land for food security. This paper aims to identify climate change and food security among the coastal community of Gili Gede Island. The research method uses qualitative with a case study approach. Data collection methods include observation, interviews, FGDs, and documentation. The research informants come from fishermen, housewives, tourism operators, village officials, and the community. The study results show that climate change impacts the social, economic, and cultural aspects as well as the food security of the community. The interaction of dependence on the mainland for food consumption not produced in Gili Gede has increased, leading to a rise in waste volume, while waste management in Gili Gede itself remains minimal. The clean water crisis has worsened over the past 5 years, with the worst being in 2023 due to the impact of El Nino. The results of this research contribute to the development of coastal areas, particularly in the sectors of coastal community development and tourism on Gili Gede Island. These findings also provide an understanding of the portrait of food vulnerability caused by climate change, which has a domino effect on income, social relations, culture, and social inequality.